(untitled) (European Journal of Health Research, 2017)
Alcohol consumption is associated with numerous harmful consequences for health, as well as broad sequelae for society. According OECD data, Portugal was, in 2014, the 15th largest consumer in the European Union. For the alcohol consumption concurences beliefs, myths and preconceptions about their effects. This a mixed nature study, observational, transversal and analytical research-action. The objective was to identify a set of myths about alcohol consumption among the student population of basic and secondary education. It was carried out in schools in the Bajo Alentejo sub-region (Portugal), where data from the National Health Survey 2005-2006 indicate to a growth in the prevalence of alcohol users. A questionnaire was applied, obtaining 501 valid answers from students at the end of basic education and secondary education. The results reveal that many myths about alcohol consumption continue to be present among students, and there is a need to define and implement an intervention plan to prevent the consumption of alcoholic beverages, which makes it possible to clarify the students about the myths, since they are inducers of consumption by misconceptions.